Cognitive dysfunction in animal models of human lewy-body dementia - Haikal, Caroline; Winston, Graham M.; Kaplitt, Michael G. (Frontiers in Aging Neuroscience, 2024)
Cognitive impairments are a common feature of synucleinopathies such as Parkinson’s Disease Dementia and Dementia with Lewy Bodies. These pathologies are characterized by accumulation of Lewy bodies and Lewy neurites as well as neuronal cell death. Alpha-synuclein is the main proteinaceous component of Lewy bodies and Lewy neurites. To model these pathologies in vivo, toxins that selectively target certain neuronal populations or different means of inducing alpha-synuclein aggregation can be used. Alpha-synuclein accumulation can be induced by genetic manipulation, viral vector overexpression or the use of preformed fibrils of alpha-synuclein. In this review, we summarize the cognitive impairments associated with different models of synucleinopathies and relevance to observations in human diseases.